The Significance of Birds in the Works of Augusto Roa Bastos - Helene C. Weldt-Basson (Studies in 20th & 21st Century Literature, 2009)
Birds have occupied a central role in the works of the Paraguayan writer, Augusto Roa Bastos (1917-2005), from the beginning of his literary career. In texts ranging from his early poetry to his complete short stories, compiled in 2003, the bird motif repeatedly resurfaces, raising the question of the relevance of birds in Roa Bastos’s oeuvre. This article argues that birds are used symbolically throughout Roa Bastos’s poetry and prose works, by drawing upon their significance within Guarani myths and literature. The article focuses on several symbolic associations for birds in Guarani culture, including their relationship to oral language, their prophetic value, their association with thunderstorms, and their view of the owl as an ambiguous creature that signifies both death and rebirth. This article studies Roa Bastos’s poetry, the short stories “El pájaro-mosca” ‘The Hummingbird,’ “Cuando un pájaro entierra sus plumas” ‘When a Bird Buries its Feathers,’ “El país donde los niños no querían nacer” ‘The Country Where Children Didn’t Want to be Born,’ and the novels Yo el Supremo ‘I The Supreme,’ Vigilia del almirante ‘The Admiral’s Vigil,’ and Madama Sui ‘Madame Sui.’
Keywords: birds; Augusto Roa Bastos; Paraguayan literature; Paraguay; poetry; short stories; symolism; Guarani myths; Guarani literature; El pájaro-mosca; cuando un pájaro entierra; sus plumas; el país donde los niños no querían nacer; Yo el Supremo; Vivilia del almirante; Madama Sui